Genetic variation in the small bivalve Nuculana inaequisculpta along a retreating glacier fjord, King George Island, Antarctica (Revista de Biología Marina y Oceanografía, 2021)
Climate change is strongly influencing regions of Antarctica but the consequences on microevolutionary processes have been little studied. Patterns of population genetic diversity were analysed in the Antarctic bivalve Nuculana inaequisculpta (Protobranchia: Nuculanidae) from a fjord with 70 years of documented climate-forced glacier retreat. Thirty-nine individuals from five sites at different distances from the glacier terminus were collected, and the COI gene was sequenced from each individual. No statistically significant genetic differentiation was found between sites nor a significant correlation between the proximity of glaciers and genetic diversity, suggesting a high dispersal capability and therefore, a planktonic larval stage for this species. Nevertheless, we encourage increasing the sample size and number of loci in future studies to confirm our findings.